THE Concept Of Tawhid-Based Curriculum In The Perspective Of Islamic Education Philosophy According to Al-Qur'an And Hadith - Hamdi, Liwaul Hamdi Liwaul (AL MURABBI, 2023)
The curriculum in Islamic education has a central role in shaping the character, morality and spirituality of individuals. In the perspective of Islamic Philosophy of Education, the concept of tawhid-based curriculum, in accordance with the teachings of the Qur'an and Hadith, shows the urgency of integrating tawhid values in every aspect of learning. The main focus of this concept is to introduce, explore, and apply the concept of the oneness of God in education. The Qur'an and Hadith become the main philosophical foundation that guides curriculum development, emphasizing that tawhid is not only an aspect of belief, but also the foundation for the formation of a moral and spiritually strong character. Through this approach, tawhid-based Islamic education not only teaches academic knowledge, but also leads to a holistic transformation of students' lives. The curriculum emphasizes the importance of developing spiritual, critical and analytical skills in understanding Islamic teachings, while guiding students to apply the values of tawhid in the context of everyday life. Thus, the concept of tawhid-based curriculum in the perspective of Islamic Philosophy of Education provides a strong foundation to form individuals who are faithful, noble, and able to apply Islamic teachings in their lives.